PENGARUH PERSON ORGANIZATION FIT DAN LOCUS OF CONTROL DENGAN MEDIASI KOMITMEN ORGANISASIONAL TERHADAP KINERJA PEGAWAI PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK. CABANG KUDUS (Students' Journal of Accounting and Banking, 2013)
This research aims to examine and describe the effect of person organization fit, locus of control, and organizational commitment towards the performance of PT. Bank Rakyat Indonesia (Persero) Tbk Kudus Branch. This research was conducted on PT. Bank Rakyat Indonesia (Persero) Tbk Kudus Branch employees. The technique that is used is the purposive sampling method. The data testing technique that is used in this research covers the validity test with the factor analysis, reliability test with the Alpha Cronbach, the analysis using Adjusted R Square Testing Model, Fit Model Test, Regression Analysis, Hypothesis Analysis, and Mediation Test. The analysis and discussion results from this research show that the person organization fit, locus of control and organizational commitment have positive effect to wards the employees’ performance on PT. Bank Rakyat Indonesia (Persero) Tbk Kudus Branch. Keywords: Person Organization Fit, Locus of control, Organizational Commitment and Employee